Analysis of SOX1 regulation in stem cell and cancerous cell lines - Ahmad, Azaz (2017)
The SOX family of transcription factors are well-known regulators of diverse cellular events during development. SOX1, which belongs to the SOXB1 sub-family, is a key regulator of neural stem cell fate and a known specific marker of the neuroectoderm lineage. SOX1 plays an important role in early embryonic and postnatal CNS development. Recently, several studies have implicated SOX1 as a tumour suppressor gene in different cancer types. Conversely, SOX1 has also been reported to act as an oncogene in a prostate cancer model. In order to better understand SOX1 gene regulation, this project set out to gain a deeper insight into the regulation of SOX1 in the context of stem cells and cancer, and to identify potential regulatory mechanisms that can significantly regulate its function.